Bioinformatic analysis of the pathogenic mechanism of talaromyces marneffei infection. Issue 48 (25th November 2020) - Cen, Jiemei; Chen, Jiarui; Qiu, Ye; Zeng, Wen; Zhang, Jianquan
Abstract: Background: Talaromyces marneffei (T marneffei), known as a significant pathogen in patients with AIDS in Southeast Asia, is a dimorphic fungus, which can cause deadly systematic infection in immunocompromised hosts. What is more, the dimorphic phase transition has been reported as a conspicuous process linked with virulence. Interestingly, the yeast form was found in infected individuals, representing the pathogenic phase. However, few researches were found to study the mechanism of dimorphic transition. Thus, a diverse insight into the dimorphic switch mechanism, is urgently needed and we are the first one to research the mechanism of dimorphism. Methods: Firstly, we investigated the microarray of T. marneffei in the Gene Expression Omnibus database (GEO) for differentially expressed genes (DEGs). Then Database for Annotation, Visualization and Integrated Discovery (DAVID) v6.8 was employed to analyze the underlying enrichment and pathway in biological process of DEGs. Meanwhile, protein-protein interaction (PPI) network was constructed using STRING database. On the strength of the theory that similar amino acid sequences share similar structures, which play a decisive role on the function of protein, three dimensional structures of hub-genes were predicted to further investigate the likely function of hub-genes. Results: GSE51109 was elected as the eligible series for the purpose of our research, including GSM1238923 (GSM23), GSM1238924 (GSM24), and GSM1238925 (GSM25). PMAA_012920, PMAA_028730, PMAA_068140, PMAA_092900, PMAA_032350 were the most remarkable genes in all of the three PPI networks, thus, were viewed as hub-genes. With regard to the three-dimensional construction, except that there was no significant prediction structure of PMAA_092900 with the criterion seq identify > 30%, GMQE: 0-1, QMEAN4: -4-0, the parallel templates for four structures were Crystal structure of Saccharomyces cerevesiae mitochondrial NADP(+)-dependent isocitrate dehydrogenase in complex with isocitrate, Organellar two-pore channels (TPCs), Yeast Isocitrate Dehydrogenase (Apo Form) and Crystal Structure Of ATP-Dependent Phosphoenolpyruvate Carboxykinase From Thermus thermophilus HB8 in order. Conclusion: The dimorphic transition of T. marneffei was viewed as a pathogenic factor and DEGs were observed. In-depth study of the function and pathway of DEGs revealed that PMAA_012920, PMAA_028730, PMAA_068140, PMAA_092900, PMAA_032350 were most likely acting as the hub-genes and were likely taking effect through regulating energy metabolism.